Ethical AI in EFL Writing Instruction: A Case Study of Lecturers’ Communication and Pedagogical Strategies - Farida Noor Rohmah; Setya Putri Rahayu (Universitas Hamzanwadi, 2025)
The rapid integration of large language models such as ChatGPT into higher education creates new opportunities for EFL writing instruction but also raises complex ethical and pedagogical challenges. While existing research has largely focused on students’ use of AI, comparatively little is known about how lecturers themselves navigate its ethical implications in writing classes. This qualitative case study investigates the experiences of two EFL academic writing lecturers at a private university in Yogyakarta, Indonesia. Data were generated through semi-structured interviews and document analysis of course syllabi and Learning Management System (LMS) materials, and were examined using thematic analysis. Three interrelated themes emerged: communication approaches, pedagogical strategies, and challenges identified. The lecturers used open dialogue, explicit ethical framing, and reflective discussion to position ChatGPT as a supplementary tool rather than a substitute for students’ thinking. They also designed guided exploration and scaffolded integration tasks, such as AI–human text comparison and critical evaluation of AI outputs, to foster AI literacy and metacognitive awareness. However, they reported significant obstacles, including students’ overreliance on AI-generated text, uneven AI literacy, and limited institutional guidance, with formal documents treating ChatGPT mainly as a percentage-based rubric rather than a pedagogical resource. The findings underscore the need for intentional, ethics-informed instructional design and coherent institutional policies. The study concludes that ongoing professional development and clearer AI-related regulations are essential for enabling EFL lecturers to cultivate responsible AI use and sustain academic integrity in AI-augmented writing environments.